Gewerkschaftsmacht und ihre Grenzen Die ÖTV und ihr Vorsitzender Heinz Kluncker 1964-1982 - Führer, Karl Christian (Forschung aus der Hans-Böckler-Stiftung, 2017)
An exemplary study about the work and power of unions in the young Federal Republic of Germany.